Persistence of excitation for identifying switched linear systems. (March 2022) - Mu, Biqiang; Chen, Tianshi; Cheng, Changming; Bai, Er-wei
Abstract: This paper investigates the uniqueness of parameters via persistence of excitation for switched linear systems. The main contribution is a much weaker sufficient condition on the regressors to be persistently exciting that guarantees the uniqueness of the parameter sets and also provides new insights in understanding the relation among different subsystems. It is found that for uniquely determining the parameters of switched linear systems, the needed minimum number of samples derived from our sufficient condition is much smaller than that reported in the literature.